A new genus and species of Serpulidae (Annelida, Polychaeta, Sabellida) from the Caribbean Sea - Prentiss, Nancy K.; Vasileiadou, Katerina; Faulwetter, Sarah; Arvanitidis, Christos; Hove, Harry A. Ten (Zootaxa, 2014)
A new genus and species of Serpulidae (Annelida, Polychaeta) from the Caribbean Sea. Turbocavus secretus (gen. nov. and sp. nov.) is described from shallow hard substrates (0.5–3 m) in wind-sheltered bays of St. John, U.S. Virgin Islands and Curaçao, as well as from diving depths (46−49 m) around Bonaire (Leeward Antilles), Caribbean Sea. The new taxon, which has from 7 to 19 thoracic chaetigers and up to 335 abdominal chaetigers, bears a unique type of thoracic chaeta which is multifolded at the base and continues with a groove tapering to the capillary tip. The new serpulid has unique 18S rRNA sequences and genetic analysis of the 18S rRNA gene situates the new genus at the basis of the serpulid cladogram, well separated from other genera, and close to Filograna/Salmacina and Protula.